EFFECTIVENESS OF KAFFIR LIME (Citrus hystrix D.C.) AND BASIL (Ocimum sanctum L.) LEAF POWDER ON Callosobruchus chinensis L. (Coleoptera; Chrysomelidae) MORTALITY IN GREEN BEANS - Pramono, Sudi; Helina, Selvi; Purnomo, Purnomo; Damayanti, Fransisca (Departement of Agrotechnology, Agriculture Faculty, Universitas Lampung, 2025)
Storage can determine the quality of green beans, therefore, to prevent the product from being attacked by warehouse pests, good storage and packaging are needed. The main pest that attacks green beans during storage is Callosobruchus chinensis L. This study aims to test the effectiveness of kaffir lime leaves and basil against Callosobruchus chinensis L. pests and weight loss of green bean seeds attacked by C. chinensis. This study used a completely randomized design (RAL) with 4 treatments and 4 replications, namely control, kaffir lime leaves 8 g, 10 g, and 12 g, basil leaves 8 g, 10 g, and 12 g. The data obtained were analyzed using a 5% level of ANARA and then continued with a 5% DMRT test. The results obtained after 28 HSA observations were that kaffir lime leaf powder at a dose of 12 g caused the highest C. chinensis mortality and the lowest reduced the weight loss of green beans. Basil leaf powder treatment at a dose of 12 g caused the highest C. chinensis mortality and the lowest reduction in green bean weight loss for 28 HSA. This research shows that kaffir lime leaves and basil have the potential to control C. chinensis during storage.